2018
DOI: 10.1088/1361-6560/aa9e1b
|View full text |Cite
|
Sign up to set email alerts
|

Objective image characterization of a spectral CT scanner with dual-layer detector

Abstract: This work evaluated the performance of a detector-based spectral CT system by obtaining objective reference data, evaluating attenuation response of iodine and accuracy of iodine quantification, and comparing conventional CT and virtual monoenergetic images in three common phantoms. Scanning was performed using the hospital's clinical adult body protocol. Modulation transfer function (MTF) was calculated for a tungsten wire and visual line pair targets were evaluated. Image noise power spectrum (NPS) and pixel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…However, the mean CT energy spectrum was not known exactly and had to be approximated. Based on preliminary experiments, 72 keV were used for 120 kVp imaging, which was in good agreement with previous dual energy CT studies, where 120 kVp single energy images yielded similar HU values as 70–75 kVe monochromatic images 13–16 . Calculated HU values were in excellent agreement with measured values, confirming the validity of the calculation model.…”
Section: Discussionsupporting
confidence: 84%
“…However, the mean CT energy spectrum was not known exactly and had to be approximated. Based on preliminary experiments, 72 keV were used for 120 kVp imaging, which was in good agreement with previous dual energy CT studies, where 120 kVp single energy images yielded similar HU values as 70–75 kVe monochromatic images 13–16 . Calculated HU values were in excellent agreement with measured values, confirming the validity of the calculation model.…”
Section: Discussionsupporting
confidence: 84%
“…The latest dual-layer spectral detector CT (SDCT) acquires homologous, in-phase, and temporally synchronized photons from a single source, thereby enabling energysensitive projection data to be obtained simultaneously. The system applies anti-correlated noise suppression and an iterative algorithm, thus reducing image noise and improving image quality (10)(11)(12). Another advantage that SDCT has over other types of dual-energy CT is that it can generate all spectral datasets without the need to pre-set dual-energy protocols, thereby efficient clinical workflow (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…First, the conspicuous texture of low-energy virtual monochromatic images is problematic. A previous report showed that monochromatic images at 70 keV have similar texture to conventional CT images acquired at 120 kVp and the texture becomes noticeable on 50-keV images [17] . Therefore, conspicuous image texture as shown in case 3 ( Fig.…”
Section: Discussionmentioning
confidence: 80%